Exploring Tolerance-Related Socio-Emotional Practices through BCCT and DAP in Early Childhood Education: An Exploratory Qualitative Case Study - Mursid, Mursid; Muna Fatmawati, Nilal (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study aims to explore how the Beyond Centers and Circle Time (BCCT) approach and Developmentally Appropriate Practice (DAP) principles are integrated in classroom practices to support tolerance as a socio-emotional competence in early childhood education.Design/methods/approach – This study employed an exploratory qualitative case study design at RA Hj. Sri Musiyarti Semarang. Data were collected through non-participant classroom observations, structured and semi-structured interviews with the principal and teachers, and documentation of learning activities involving 15 children aged 5-6 years. Data were analyzed using the Miles, Huberman, and Saldana interactive model through data condensation, data display, and conclusion drawing. Credibility was strengthened through methodological and source triangulation, member checking, and systematic field notes.Findings – The findings suggest that BCCT and DAP interacted as complementary classroom conditions rather than as a measurable intervention effect. BCCT provided structured opportunities for social encounters through learning centers, circle time, teacher scaffolding during play, and recalling after play. DAP shaped how teachers adjusted activities, language, expectations, and mediation to children's developmental characteristics. Within this classroom context, tolerance-related behaviors were observed in sharing, cooperation, empathy, appreciation of different ideas or products, and simple conflict negotiation. However, these behaviors remained situated and teacher-mediated, indicating that tolerance in early childhood should be interpreted as an emerging socio-emotional practice rather than a stable competence already internalized by children.Research implications/limitations – The study offers contextual insight into how center-based and developmentally responsive practices may create opportunities for children to practice tolerance-related behaviors. Its findings are limited to a single institutional case, a short period of fieldwork, and school-based observations; therefore, they are not intended for broad generalization or claims of effectiveness.Practical implications – The findings provide practical guidance for early childhood educators in designing inclusive learning environments that promote tolerance through meaningful social interactions.Originality/value – This study offers a contextual pedagogical interpretation of the relationship between BCCT, DAP, and tolerance-related socio-emotional practices in early childhood education. It shifts the discussion from abstract tolerance education toward the situated classroom processes through which children encounter, negotiate, and practice respect for others during play-based learning.Paper type Research paper